Analysis of Causes and Impacts of Tug and Barge Vessel Accidents Using the Analytic Hierarchy Process: A Case Study of XYZ Company - Mohammad Danil Arifin; Mohammad Fajar Sodiq; Aldyn Clinton Partahi Oloan; Y. Arya Dewanto; Fanny Octaviani (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2026)
Indonesia’s maritime sector plays a strategic role in national logistics, where tug and barge vessels are widely used to transport bulk commodities due to their cost efficiency and operational flexibility. However, tug and barge operations face a high risk of accidents, particularly in densely trafficked waterways and challenging environmental conditions. This study aims to analyze the causes and impacts of tug and barge vessel accidents at Company XYZ during the period 2015–2024 and to determine priority mitigation measures using the Analytic Hierarchy Process (AHP). The study analyzes 170 recorded accident cases classified into human, technical, environmental, and procedural factors. The results show that human factors are the dominant cause, contributing 55.8% of accidents, followed by technical factors (26.3%), environmental factors (12.2%), and procedural factors (5.7%). The accidents resulted in material losses, operational delays of 3–7 days per incident, and environmental impacts such as fuel spills and onboard fires. The AHP results indicate that human-related factors are the highest priority for mitigation, followed by technical, environmental, and procedural factors, with a consistency ratio of 0.043, indicating acceptable reliability. This study provides a structured decision-making approach to support safety improvement and risk mitigation in tug and barge vessel operations.